Transoral approach to the craniovertebral junction Acesso transoral para a junção craniocervical - José Alberto Landeiro; Sávio Boechat; Daniel de Holanda Christoph; Mariângela Barbi Gonçalves; Igor de Castro; Mario Alberto Lapenta; Carlos Henrique Ribeiro (Arquivos de Neuro-Psiquiatria, 2007)
The transoral approach provides a safe exposure to lesions in the midline and the ventral side of the craniovertebral junction. The advantages of the transoral approach are 1) the impinging bony pathology and granulation tissue are accessible only via the ventral route; 2) the head is placed in the extended position, thus decreasing the angulation of the brainstem during the surgery; and 3) surgery is done through the avascular median pharyngeal raphe and clivus. We analyzed the clinical effects of odontoidectomy after treating 38 patients with basilar invagination. The anterior transoral operation to treat irreducible ventral compression in patients with basilar invagination was performed in 38 patients. The patients’ ages ranged from 34 to 67 years. Fourteen patients had associated Chiari malformation and eight had previously undergone posterior decompressive surgery. The main indication for surgery was significant neurological deterioration. Symptoms and signs included neck pain, myelopathy, lower cranial nerve dysfunction, nystagmus and gait disturbance. Extended exposure was performed in 24 patients. The surgery was beneficial to the majority of patients. There was one death within 10 days of surgery, due to pulmonary embolism. Postoperative complications included two cases of pneumonia, three cases of oronasal fistula with regurgitation and one cerebrospinal fluid leak. In patients with marked ventral compression, the transoral approach provides direct access to the anterior face of the craniovertebral junction and effective means for odontoidectomy. O acesso transoral é uma via direta e segura às lesões situadas na linha média e na face anterior da junção craniocervical. As vantagens do acesso transoral são as seguintes:1) a compressão óssea e o tecido de granulação localizam-se anteriormente e são accessíveis pela via anterior; 2) a cabeça do paciente é colocada em extensão, diminuindo a angulação do tronco cerebral durante a cirurgia; e 3) a cirurgia é feita através de um plano avascular na linha média faríngea e clivo. Analisamos os resultados obtidos após odontoidectomia por via transoral em 38 pacientes portadores de invaginação basilar. Trinta e oito pacientes com compressão ventral da junção craniocervical foram submetidos a odontoidectomia por via transoral. A idade dos pacientes variou de 34 a 67 anos. Quatorze pacientes apresentavam associação com malformação de Chiari tipo I e 8 já haviam sido submetidos à cirurgia descompressiva por via posterior. A maioria dos pacientes apresentou nucalgia, mielopatia, déficits dos nervos cranianos baixos, nistagmo, e distúrbio da marcha. Em 24 pacientes foi necessário ampliar o acesso transoral através de miotomia do palato mole, ou osteotomia do palato duro ou maxilotomia. A cirurgia proporcionou melhora dos sintomas na maioria dos pacientes. Um paciente faleceu no pós-operatório imediato por causa de embolia pulmonar. Dois pacientes tiveram pneumonia, três apresentaram fístula oronasal com regurgitação, e um teve fístula liquórica. Em pacientes com compressão ventral irredutível da junção craniocervical, a via transoral proporcionou uma abordagem direta e ampla ao processo odontoide.